2021
DOI: 10.1002/pca.3057
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterisation of xanthine oxidase inhibitors from the flowers of Chrysanthemum morifolium Ramat. Using metabolomics approach

Abstract: Introduction Hyperuricemia is the key risk factor for gout, in which the elevated uric acid is attributed to the oxidation of hypoxanthine and xanthine to uric acid by xanthine oxidase (XO). Adverse effects of the current treatments lead to an urgent need for safer and more effective alternative from natural resources. Objective To compare the metabolite profile of Chrysanthemum morifolium flower fraction with that of its detannified fraction in relation to XO inhibitory activity using a rapid and effective me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Phytochemical analyses have identified polyphenolic compounds such as coumaric acid and ferulic acid as biologically active compounds in A. distichum (Kim and Lee, 2015;Choi et al, 2017;Yoo et al, 2021). In addition, positive and strong correlations between the polyphenolic contents of EtOAc fractions and their pharmaceutical activities have been reported in various plant extracts (Kim et al, 2014;Tinco-Jayo et al, 2021;Loh et al, 2022). Therefore, we hypothesized that MeJA improves the production of polyphenolic compounds, resulting in enhanced antiinflammatory effects of AdAR.…”
Section: Effect Of Etoac/meja On the Mitogenactivated Protein Kinase ...mentioning
confidence: 96%
“…Phytochemical analyses have identified polyphenolic compounds such as coumaric acid and ferulic acid as biologically active compounds in A. distichum (Kim and Lee, 2015;Choi et al, 2017;Yoo et al, 2021). In addition, positive and strong correlations between the polyphenolic contents of EtOAc fractions and their pharmaceutical activities have been reported in various plant extracts (Kim et al, 2014;Tinco-Jayo et al, 2021;Loh et al, 2022). Therefore, we hypothesized that MeJA improves the production of polyphenolic compounds, resulting in enhanced antiinflammatory effects of AdAR.…”
Section: Effect Of Etoac/meja On the Mitogenactivated Protein Kinase ...mentioning
confidence: 96%
“…In particular, the ability to inhibit XOD has been investigated for a large number of molecules including caffeic acid [ 12 ], apigenin, quercetin, luteolin [ 13 , 14 ], kaempferol [ 15 ], rutin [ 16 ], chlorogenic acid [ 17 ], sinapic acid [ 18 ], phloroglucinol derivatives [ 19 ], and polyphenol-rich plant extracts [ 20 , 21 ]. Among the latter, extracts from tea leaves, Tartary buckwheat, Chrysanthemum morifolium, Smilax china L., Flourensia fiebrigii, and Keladi Candik, that contain a mix of many different bioactive compounds, have shown a high XOD inhibitory activity [ 22 , 23 , 24 , 25 , 26 ]. Molecular docking studies have demonstrated that these compounds can interact with some XOD amino acid residues, forming a complex which effectively interferes with the enzyme activity [ 11 , 15 , 27 ].…”
Section: Beneficial Effect Of Bioactive Compounds In Gout and Hyperur...mentioning
confidence: 99%
“…The dried flower part of chrysanthemum can be used as a natural xanthine oxidase (XOD) inhibitor to alleviate hyperuricemia and other related diseases. C. morifolium Boju extract (CBE) can inhibit the activity of serum XOD, reduce the levels of indohydroxyl sulfate, lysophosphatidylcholine, and arachidonic acid (AA), alleviate chronic kidney disease, hyperlipidemia, inflammation, and other hyperuricemia‐related diseases, and effectively improve hyperuricemia (Loh et al, 2022; Peng et al, 2019).…”
Section: Medicine and Food Homologous Flowers And Diseasesmentioning
confidence: 99%